On the economic determinants of oil production: Theoretical analysis and empirical evidence for small exporting countries - Alessandro Cologni; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2011)
In this paper, decisions regarding production in oil exporting countries are studied by means of theoretical analysis and empirical investigation. Under the assumptions of exogenous oil prices and world oil demand, we are able to describe the relationship between oil production levels and changes in the conditions in world oil markets. Intertemporal production decisions by a representative oil producer are modelled by means of a partial equilibrium model. In this theoretical model, oil producers are subject to exogenous shocks in world oil demand and prices. Oil companies can change output levels only by incurring a fixed cost. Results from the simulation of this model show a strong relationship between oil production and changes in world oil consumption. On the contrary, the effects of changes in real oil prices on oil production decisions seem to be much lower. Results from the simulation of the theoretical model are then empirically investigated using time-series econometric techniques. The empirical evidence supports the hypothesis that several oil producing countries are characterized by different responses to changes in world oil demand and in real oil prices. For many countries production rapidly adjusts to changes in consumption whereas responses of oil production to innovations in real oil prices are found to be not statistically significant. In addition, when non-linearities in the relationship between exogenous variables and output levels are allowed for, evidence of asymmetric effects of output levels to shocks in demand levels and oil prices is found.
Keywords: C22; D21; D22; Q41; 330; Oil Production; Exogenous Shocks; Theoretical Modelling; Time Series Analysis